Advances in polyolefin nanocomposites - Mittal, Vikas (Boca Raton : CRC Press, 2011)
'With the advent of polymer nanocomposites, research on polyolefin nanocomposites has grown exponentially. Correcting the deficiency of a meaningful text on these important materials,Advances in Polyolefin Nanocomposites: Sums up recent advances in nanoscale dispersion of filler in polyolefins Presents a basic introduction to polyolefin nanocomposite technology for the readers new to this field Provides insights on the use of technologies for polyolefins nanocomposites for commercial application Includes contributions from the most experienced researchers in the field Offers insights into the commercial usage of techniques The text uses theoretical models to illustrate the organic-inorganic interfaces in polyolefins and also provides a detailed description of the recently developed models for property prediction of these nanocomposites. It concentrates on developments with not only aluminosilicate fillers, but also with equally important fillers like layer double hydroxides and nanotubes. The authors review polyolefin nanocomposite technology and methodologies of generation, properties and generation of composite blends, and advances in synthesis of nanocomposites using solution blending methods. The book covers theoretical and experimental considerations of clay surface modification and the importance and effect of various prominent filler categories'--
Includes bibliographical references and index.
Keywords: Polyolefins; Nanocomposites (Materials).; Fillers (Materials).